A imaginária religiosa de Goiás: o reconhecimento de Veiga Valle e o anonimato dos santeiros goianos (1820-1940) - Machado, Raquel de Souza (2016)
This Master's Thesis, entitled “The Sacred Art in Goiás: the recognition of the work of Veiga Valle and the other anonymous saint makers (1820-1940)”, presents the results of the field research and the literature review about the saint makers from the state of Goiás, Brazil, that remained under the shadow of José Joaquim da Veiga (1806-1874) during the 19th century and the beginning of the 20th century. Hence, the considered period of the artistic production starts in 1820 and ends in 1940. In spite of not including a secular historical study, this work deals with the biographies of the artists and their art works. Regarding the religious iconographic representations, only those that are relevant to the role of saint makers, related to the considered period, are analyzed. Basically, the text discuss the saint makers role as creators of either original or non-original art works that represent not only their own subjectiveness but also the collective spirit of their time. In addition, the aim is to determine the relations between history and art history in terms of saint makers art and to understand the language associated to the images and their potential for the comparative analyses of the works. Initially, the objective was to develop a comparative study between the works by Veiga Valle and his son Henrique Ernesto da Veiga Jardim (1849-1933). However, the conducted research revealed other saint makers from the state of Goiás that deserve recognition as well. Hence, the goal was slightly modified into the discoveries of their works, their location and the authorship corroborating documents. In the cities of Goiás, Pirenópolis, Goiânia, Jaraguá and Cuiabá, the empirical research and interviews were developed based on the methodology of the oral history. Among the most relevant saint makers from the state of Goiás, one can mention Antonio de Sá (1879- 1905) and Francisco Ignácio da Luz (1821-1878), both from the city of Pirenópolis, Henrique Ernesto Veiga Jardim and Sebastião da Silva Jesus, this one known as Sebastião Epifânio (1869-1937) from the city of Vilas Boas. In order to understand the sacred art in Goiás, it is important to define a group of images for the iconographic study, namely, the sculptures of God Boy, that were chosen not only due to their presence during religious celebrations, but also because they were made in significant numbers by Veiga Valle and the other studied saint makers. Only Francisco Ignácio has never carved or even there is no sign about such event. The aim of this research is to focus on some concepts related to the art history and to demonstrate the interpretation about the found discoveries, once the history itself shows distinct versions and seeks an approximation with the truth, the verisimilitude. Through the collection of documents and iconographic analysis, the research was conducted towards to reveal anonymous saint makers, to valorize their art works, a heritage of the cultural patrimony from the state of Goiás. Additionally, these sacred art works have great devotional meaning and nowadays they are also considered as artistic objects. Most of these works can be found in either private collections or even are exposed in museums and churches.